How things fall apart : what happened to the Cuban revolution - Dore, Elizabeth (Duke University Press, 2023)
"In How Things Fall Apart Elizabeth Dore reveals the decay of the Cuban political system through the lives of seven ordinary Cuban citizens. Born in the 1970s and 1980s, they recount how their lives changed over a tumultuous stretch of thirty-five years: first when Fidel Castro opened the country to tourism following the fall of the Soviet bloc; then when RauÌ¹l Castro allowed market forces to operate; and finally when President Trump's tightening of the US embargo combined with the COVID-19 pandemic caused economic collapse. With warmth and humanity, they describe learning to survive in an environment where a tiny minority has grown rich, the great majority has been left behind, and inequality has destroyed the very things that used to give meaning to Cubans' lives. In this book, everyday Cubans illuminate their own stories and the slow and agonizing decline of the Cuban Revolution"--